Strategi Pengembangan Agrowisata Segening di Desa Pancasari Kecamatan Sukasada Kabupaten Buleleng (Jurnal Agribisnis dan Agrowisata, 2025)
Development Strategy of Segening Agrotourism in Pancasari Village, Sukasada District, Buleleng Regency. Segening Agrotourism is managed by the Segening farmer group in Pancasari Village, Sukasada District, Buleleng Regency. This agrotourism is aimed at every group, both individuals and families who want to try nature tourism, namely picking strawberries directly. This study aims to identify internal factors and external factors owned by Segening Agritourism and later determine alternative agritourism development strategies. The data analysis used is IFAS Matrix analysis, EFAS Matrix, IE Matrix and SWOT Matrix. The results showed that internal factors had seven strength factors and six weakness factors. While external factors there are five opportunity factors and three threat factors. The results of the IFAS analysis show that the highest score of strength factors is farmers who are friendly to visiting tourists and the main weakness is the limited toilet and shop facilities. While the results of the EFAS analysis, the main opportunity factor is the interest of visitors to come back at a later time and the main threats faced are competition with similar agritourism and erratic rainfall and climate. The results showed that Segening Agrotourism has moderate internal conditions and a high ability to take advantage of opportunities and overcome threats from external parties. The results of the SWOT analysis obtained two SO alternative strategies, two WO alternative strategies, one ST alternative strategy, and one ST alternative strategy.
Keywords: agrotourism; strategy; strawberry; development